“I LOVE THIS PHOTO! I CAN FEEL THEIR HEARTS”. HOW USERS ACROSS THE WORLD EVALUATE SOCIAL MEDIA PORTRAITURE - Trillò, Tommaso; Hallinan, Blake; Green, Avishai; Kim, Bumsoo; Mizoroki, Saki; Scharlach, Rebecca; Frosh, Paul; Shifman, Limor (AoIR Selected Papers of Internet Research, 2023)
Personal portraits on social media are value-laden constructs. Whether documenting graduation or flexing in the gym, users express what they care about and present it for others to evaluate. Since “global” portrait genres are produced and consumed in different locales, their interpretation and evaluation may vary. We thus ask: What values do people identify in different types of social media portraits? Which evaluative criteria do they use when judging them? An analysis of 100 interviews with users from Germany, Italy, Japan, South Korea, and the United States reveals that people consistently recognize genre-specific values in portraits and evaluate them through a narrow set of communication-related criteria. Such evaluations vary somewhat cross-culturally in ways that only occasionally match established comparative literature on values. We reflect on the relational character of the criteria adopted for the evaluation of portraits worldwide, highlighting its association with new modes of sociability in digital spheres.